'Staring into All Their Yellow Eyes': Where the Wild Things Are, the 1960s, and the Vietnam War. Issue 1 (July 2017) - Abate, Michelle Ann; Fletcher, Sarah Bradford
Abstract : Since its release in 1963, Maurice Sendak's Where the Wild Things Are has been viewed from a psychological perspective as a literary representation of children's inner emotional struggles. This essay challenges that common critical assessment. We make a case that Sendak's classic picturebook was also influenced by the turbulent era of the 1960s in general and the nation's rapidly escalating military involvement in Vietnam in particular. Our alternative reading of Sendak's text reveals a variety of both visual and verbal elements that recall the conflict in South East Asia and considers the significance of the book's geo-political engagement.